1995
DOI: 10.2307/2626957
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Coping, and Social Support Processes: Where Are We? What Next?

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.American Sociological Association is collaborating with JSTOR to digitize, preserve and extend access to Journal of Health and Social Behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

102
2,328
16
105

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,750 publications
(2,551 citation statements)
references
References 164 publications
102
2,328
16
105
Order By: Relevance
“…However, others have argued that it is the perception of support, as opposed to the actual support provided, that really matters. 46,47 Furthermore, our data suggest that many of the youths met their natural mentors through formal systems of care. Many of the mentors are adults that work for the child welfare, education, and mental health systems.…”
Section: Discussionmentioning
confidence: 67%
“…However, others have argued that it is the perception of support, as opposed to the actual support provided, that really matters. 46,47 Furthermore, our data suggest that many of the youths met their natural mentors through formal systems of care. Many of the mentors are adults that work for the child welfare, education, and mental health systems.…”
Section: Discussionmentioning
confidence: 67%
“…Both stress (Thoits, 1995) and CF researchers (Figley, 1995(Figley, , 2002b Kassam-Adams, 1999) have also suggested that other aspects of the formal caregiver's life can influence his or her likelihood of developing CF. For example, a history of trauma, lower social support, and an inability to cope with the demands of caregiving are thought to increase the likelihood of developing CF.…”
Section: Compassion Fatigue (Cf)mentioning
confidence: 99%
“…On the basis of Figley's (1995Figley's ( , 2002b conceptional of CF and psychosocial stress theory (Pearlin, 1989;Thoits, 1995), we included demographics, stressor exposures, and psychological resources as independent variables. The five demographic variables were gender, race/ethnicity, age, marital status, and years working in professional counseling.…”
Section: Independent Variablesmentioning
confidence: 99%
See 2 more Smart Citations